Respuesta :

Answer:

( -1,7)

Step-by-step explanation:

{ refer attachment }

Ver imagen janhavi11
bhip

Answer:

The answer would be (-1,7)

Step-by-step explanation:

Using the process of elimination we can subtract the two equations to cancel out the y variable. That is subtract the second equation from the first.

 3x + y = 4

- 2x + y = 5

  x        = -1

Now that we have found x we can substitute -1 for x into any equation for y. So, in substituting -1 for x in the  second equation we get:

2(-1) + y = 5

-2 + y = 5

y = 5 + 2

y = 7

ANSWER: (-1, 7)